2008
DOI: 10.1016/j.eurpolymj.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

HyperMacs – long chain hyperbranched polymers: A dramatically improved synthesis and qualitative rheological analysis

Abstract: . (2008) 'HyperMacs long chain hyperbranched polymers : a dramatically improved synthesis and qualitative rheological analysis.', European polymer journal., 44 (3). pp. 665-676. Further information on publisher's website:http://dx.doi.org/10. 1016/j.eurpolymj.2007.12.022 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in European Polymer Journal. Changes resulting from the publishing process, such as peer review, editing, corrections, stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 55 publications
(82 citation statements)
references
References 36 publications
4
78
0
Order By: Relevance
“…Each of these coupling reactions requires different chain-end functionality on the 'long' arm. In the case of a Williamson coupling reaction an alkyl halide is required and previous work [56] has shown that a bromide group is particularly effective. The experimental detail for the synthesis of PS90-Br is described above and follows a previous reported methodology [33,56].…”
Section: Synthesis Of the Polystyrene 'Long' Arm Macromonomer-ps90mentioning
confidence: 99%
See 4 more Smart Citations
“…Each of these coupling reactions requires different chain-end functionality on the 'long' arm. In the case of a Williamson coupling reaction an alkyl halide is required and previous work [56] has shown that a bromide group is particularly effective. The experimental detail for the synthesis of PS90-Br is described above and follows a previous reported methodology [33,56].…”
Section: Synthesis Of the Polystyrene 'Long' Arm Macromonomer-ps90mentioning
confidence: 99%
“…In the case of a Williamson coupling reaction an alkyl halide is required and previous work [56] has shown that a bromide group is particularly effective. The experimental detail for the synthesis of PS90-Br is described above and follows a previous reported methodology [33,56]. In brief the polymerization of styrene is initiated by 3-tert-butyldimethylsiloxy-1-propyllithium (in the presence of TMEDA) which carries a protected primary alcohol functionality.…”
Section: Synthesis Of the Polystyrene 'Long' Arm Macromonomer-ps90mentioning
confidence: 99%
See 3 more Smart Citations